Non-Parabolic Band Hydrodynamic Model for Silicon Quantum Wires. Issue 3 (16th April 2017) - Castiglione, Tina; Muscato, Orazio
ABSTRACT: Electron transport phenomena in silicon nanowires are investigated for square and equilateral triangle cross-sections of the wire by using an Extended Hydrodynamic model coupled to the Schrödinger–Poisson system. This model has been formulated by closing the moment system derived from the Boltzmann equation on the basis of the maximum entropy principle of Extended Thermodynamics, including scattering of electrons with acoustic and non-polar optical phonons and by considering the conduction band described by the Kane dispersion relation. Applications to the case of bulk silicon for different cross-sections of the wire are presented.